Relationship between Coping Mechanisms and Stress Levels in Patients with Diabetes Mellitus - Mira Aulia; Rosliana Dewi; Rani Fitriani Arifin (Indonesian Journal of Global Health Research, 2026)
The term "silent killer" is frequently used to describe diabetes mellitus (DM). Many sufferers of this illness are oblivious to the issue, which leads them to a point when major issues arise in the body's systems or different organs start to be impacted. This study sought to ascertain the connection between stress levels and coping strategies in individuals with diabetes mellitus. This was a cross-sectional, correlational, quantitative research. All diabetes mellitus patients in Cikondang Village, which is part of the Tipar Public Health Center's (UPTD Puskesmas) service area in Sukabumi City, made up the population. A total sample of sixty respondents was chosen. The instruments used were the Brief Coping Inventory for the coping mechanisms variable and the Perceived Stress Scale (PSS-10) for the stress level variable. The chi-square test was used in statistical analysis. The findings showed that most people had minor stress and used adaptive coping strategies. In patients with diabetes mellitus, coping strategies and stress levels are related, according to chi-square analysis, which produced a p-value of 0.016 (p<0.05). Conclusion: Patients with diabetes mellitus in Cikondang Village, within the service area of the Tipar Public Health Center (UPTD Puskesmas) in Sukabumi City, exhibit a correlation between coping strategies and stress levels.